Методи підвищення несучої здатності неоднорідного земляного полотна - Кравець, Іван; Ковальчук, Віталій (Видавництво Львівської політехніки, 2023)
The earth layer is the most responsible engineering structure of the transport industry, which acts as the foundation of roads. Safety, reliability and permissible speeds of transport units depend on the ground surface. The work presents modern soil strengthening technologies that are used in transport construction to strengthen subgrade soils by improving their physical and mechanical properties. It has been established that it is possible to increase the bearing capacity of non-homogeneous road subgrades by using geotextile materials and reinforcing the subgrade with the use of advanced "jet-grouting" technologies. One of the methods of increasing the deformability of a non-uniform road surface is the reinforcement of the surface with tubular drains.